Development of clinical pathway for mild cognitive impairment and dementia to quantify cost of age-related cognitive disorders in Malaysia - Aljunid, Syed Mohamed; Maimaiti, Namaitijiang; Ahmed, Zafar; Muhammad Nur, Amrizal; Mohamed Nor, Norashidah; Ismail, Normazwana; Haron, Sharifah Aizah; Shafie, Asrul Akmal; Salleh, Mohmad; Yusuf, Suraya; Mat Saher, Zanariah; Drahman, Ismail; et al. (Malaysian Public Health Physicians’ Association, 2014)
As the Malaysian population ages, the burden of age-related cognitive disorders such as dementia and Alzheimer’s disease will increase concomitantly. This is one of the sub-study under a research project titled by quantify the cost of age-related cognitive impairment in Malaysia, which was undertaken to develop a clinical pathway for Mild Cognitive Impairment (MCI) and Dementia. The clinical pathway (CP) will be used to support the costing studies of MCI and Dementia. An expert group discussion (EGD) was conducted among selected experts from six (6) government hospitals from different states of Malaysia, Ministry of Health, and United Nations University, International Institute for Global Health, UKM and UPM. The expert group includes psychiatrist specialists and public health medicine specialists. A total of 15 participants took part in the EGD. The group was presented with the different approach in managing MCI and Dementia. Finally, the group came to the consensus agreement on the most appropriate and efficient ways of managing the two conditions. In the EGD, an operational definition for MCI and Dementia was agreed upon and a pathway was developed for the usual practice in the Malaysian health system. A typical case used, as a reference is a 60-year-old patient referred to a memory clinic with complaint of “forgetfulness”. After three outpatient visits in the clinic, the diagnosis of MCI and Dementia could be clinically established. The clinical pathways covered all active clinical and non-clinical management of the patient over a period of one year. The experts identified the additional resources required to manage these patients for the whole spectrum of lifetime based on the expected life expectancy. The Clinical pathway (CP) for MCI and Dementia was successfully developed in EGD with strong support from practitioners in the health system. The findings will help the researchers to identify all-important clinical activities and interventions that will be included in the costing study.